Penerapan model project based learning untuk meningkatkan keterampilan berpikir tingkat tinggi pada pembelajaran IPA di kelas V sekolah dasar - Choeriyah, Rina; Poerwanti, Jenny Indrastoeti Siti; Chumdari, Chumdari (Didaktika Dwija Indria, 2024)
The purpose of this research is to (1) describe the implementation of Project Based Learning model, and (2) improve high-level thinking skills in science learning. The research is a collaborative classroom action research that conducted in two cycles. The subjects were teacher and students of V grade SDN Ngabeyan 01 Kartasura Sukoharjo. Both qualitative and quantitative data are employed. Data collection techniques used observations, interviews, and tests. Data validity testing technique used triangulation. Data analysis technique used interactive analysis. The result conclude that, (1) the implementation of Project Based Learning model in science learning appropriate the steps: (a) determining basic questions, (b) planning projects, (c) compiling project schedules, (d) supervising the project, (e) testing outcomes, and (f) evaluating; (2) the implementation of Project Based Learning model can enhance high level thinking skills on science learning in V grade SDN Ngabeyan 01 Kartasura Sukoharjo showed the satisfaction percentage of the HOTS test in cycle II was 83.33% for questions C4, C5, and C6.